Synthesis and glycosidase inhibition of the enantiomer of (-)-steviamine, the first example of a new class of indolizidine alkaloid. - Hu, X; Bartholomew, B; Nash, R; Wilson, F; Fleet, G; Nakagawa, S; Kato, A; Jia, Y; van Well, R; Yu, C (2010)
(+)-Steviamine, the enantiomer of the natural (-)-steviamine, and its corresponding C5 epimer have been synthesized from the D-ribose-derived cyclic nitrone. (-)-Steviamine was found to be the first naturally occurring iminosugar that causes any inhibition of alpha-galactosaminidases.